Is risk of Kaposi's sarcoma in AIDS patients in Britain increased if sexual partners came from United States or Africa? - Beral, V; Bull, D; Jaffe, H; Evans, B; Gill, N; Tillett, H; Swerdlow, A (1991)
OBJECTIVE: To determine whether the risk of Kaposi's sarcoma in patients with AIDS is increased by sexual contact with groups from abroad with a high incidence of Kaposi's sarcoma. DESIGN: Analysis of risk of Kaposi's sarcoma in patients with AIDS, according to country of origin of their sexual partners. SETTING: United Kingdom. PATIENTS: 2830 patients with AIDS reported to the Communicable Disease Surveillance Centre and the Communicable Disease (Scotland) Unit up to March 1990, of whom 566 had Kaposi's sarcoma. MAIN OUTCOME MEASURES: Percentage of patients with AIDS who had Kaposi's sarcoma. RESULTS: 537 of 2291 homosexual or bisexual men (23%) with AIDS had Kaposi's sarcoma; 10% (14/135) of the men and women who acquired HIV by heterosexual contact had Kaposi's sarcoma. None of the 316 subjects who acquired HIV through non-sexual routes had Kaposi's sarcoma. Kaposi's sarcoma was more common among homosexual men whose likely source of infection included the United States (171/551, 31%) or Africa (9/34, 26%) than among those infected in the United Kingdom (119/625, 19%) (p less than 0.05). CONCLUSION: The data suggest that Kaposi's sarcoma is caused by a sexually transmissible agent which was introduced into the British homosexual population mainly from the United States [corrected].